The Impact of Sustainable Agriculture on Animal Production, Food Security and Climate Change - Jaafreh, Ola Al; Nagy, Imre; Ismail, Tariq; Al-Tawaha, Abel Rahman (Revista Electronica de Veterinaria, 2023)
The sustainability of agriculture is a crucial perspective for many societal parts today. Sustainable agriculture takes into account ways to lessen the effect of climate change in both branches of the agricultural sector, both environmentally and economically, starting with the farming tools or practices that all farmers use in the farm production process in order for it to be sustainable. However, in many instances, the study of sustainable agriculture focuses solely on the effects of its application on society, including all of its constituents, as well as on how it affects the environment and the economy. This neglects the main effects and importance of sustainable agriculture parallel to the effecting of climate change on animal production and food security, which are also addressed. The purpose of the study is to mention Animal Production, Food Security and Climate Change through the existence of sustainable agriculture, this study is a review article, which is based on previous research and reports. Findings suggested that applying sustainable agriculture largely influences animal production and reducing of climate change effects.